Synergistic effect of muramyl peptide immunocorrection and prostaglandin-based vasoactive therapy in the treatment of purulent-inflammatory soft tissue diseases - Bohachuk, M. (Journal of Education, Health and Sport, 2025)
The treatment of purulent-inflammatory soft tissue diseases (PISTD) in type 2 diabetes mellitus (T2DM) patients remains a challenge due to the "regenerative plateau" phenomenon. The Purpose of the Study is to improve surgical treatment efficiency in PISTD and T2DM patients by implementing a synergistic strategy based on muramyl peptide-derived immunomodulators and prostaglandin E1 analogues to restore microcirculation and activate the macrophage-neutrophil link. Methods. A clinical study involved 148 patients (control group n=72, standard care; main group n=76, muramyl peptides + prostaglandin E1). Morphometric and immunocytochemical analyses were performed. Results. The proposed therapy eliminated capillary sludge within 2–3 days. Myeloperoxidase (MPO) activity recovered to 72.0±6.1%. Computer planimetry showed a 59.3% wound area reduction by day 10. The average hospital stay was shortened to 9.4±1.3 days (p ≤ 0.05). Conclusions. The combined approach effectively reboots tissue regeneration by synchronizing immune response and regional blood flow.